2022
DOI: 10.1021/acsomega.2c03445
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Glass Resists Based on Tetraphenylsilane Derivatives: Effect of Protecting Ratios on Advanced Lithography

Abstract: A series of t -butyloxycarbonyl ( t -Boc) protected tetraphenylsilane derivatives (TPSi-Boc x , x = 60, 70, 85, 100%) were synthesized and used as resist materials to investigate the effect of t -Boc protecting ratio on advanced lithography. The physical properties such as solubility, film-forming ability, and thermal stability of TPSi-Boc x were examined to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…Several materials, including calixarene derivatives, , polyphenols, Noria molecules, , and fullerene derivatives, have been explored as MG resists in EUV or e-beam lithography. Our recent work has led to the development of a series of MG resists based on bisphenol A, spirobifluorene, tetraphenylsilane, and adamantane derivatives , for EUV and electron beam lithography (EBL), successfully delivering patterns with high resolution and low LER. Most of the research focused on molecular CAR, while non-CAR based on MGs is relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Several materials, including calixarene derivatives, , polyphenols, Noria molecules, , and fullerene derivatives, have been explored as MG resists in EUV or e-beam lithography. Our recent work has led to the development of a series of MG resists based on bisphenol A, spirobifluorene, tetraphenylsilane, and adamantane derivatives , for EUV and electron beam lithography (EBL), successfully delivering patterns with high resolution and low LER. Most of the research focused on molecular CAR, while non-CAR based on MGs is relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of TPSi is facile. 48 , 49 Our recent research has demonstrated that MG resists based on TPSi derivatives exhibit excellent thermal stability, film-forming ability, and high-resolution pattern performances. 49 Further, a new strategy of dual-tone developed molecular resists was proposed in our report, demonstrating a promising method to improve overall lithographic performance.…”
Section: Introductionmentioning
confidence: 99%
“… 48 , 49 Our recent research has demonstrated that MG resists based on TPSi derivatives exhibit excellent thermal stability, film-forming ability, and high-resolution pattern performances. 49 Further, a new strategy of dual-tone developed molecular resists was proposed in our report, demonstrating a promising method to improve overall lithographic performance. 50 As a continuation, a novel PAG-bound MG (TPSiS) was designed and prepared by modifying TPSi with eight t -butyloxycarbonyl ( t -Boc) groups and one sulfonium salt unit ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…PAG is a photosensitive compound; in the post exposure baking (PEB) process, it will stimulate the reaction of the acid sensitive group on the main chain of the resin and generate new acid components. To improve lithography performance, the development of more advanced photoresist materials is significant. Lawson’s team designed molecules with epoxy structure and used them for negative-tone photoresist. After exposure, PAGs generate photoacid and catalyze the self-cross-linking reaction of the epoxy compounds, finally forming a dense network which drives the solubility switch. In addition, the huge cross-linked network can effectively improve the mechanical properties of the photoresist.…”
Section: Introductionmentioning
confidence: 99%